PENGARUH LITERASI DIGITAL DAN SOCIAL INFLUENCE TERHADAP ADOPSI TEKNOLOGI DIGITAL OLEH PETANI KOPI PEREMPUAN DI KABUPATEN TEMANGGUNG - Fauziah, Irma; Rahmaningtyas, Avivah; Luthfie Fadhilah, Muhammad (Universitas Veteran Bangun Nusantara, 2025)
This study aims to analyze the influence of digital literacy and social support on the adoption of digital technology among female coffee farmers in Temanggung Regency. Primary data were obtained through structured interviews using a questionnaire. The research location and respondents were determined through purposive sampling, with criteria including female farmers who are actively engaged in coffee farming activities, reside in Temanggung Regency, and have utilized digital technology to support their farming operations. The total number of respondents in this study was 70. Data were analyzed using multiple linear regression. The results show that digital literacy has a positive and significant effect on the ability of female farmers to utilize digital technology, both in accessing cultivation information and in marketing agricultural products. Meanwhile, social support has a more dominant influence in encouraging the adoption of digital technology, particularly through the influence of family members, farmer groups, agricultural extension workers, and agricultural input suppliers. These findings highlight that improving digital literacy capacity needs to be complemented by strengthening social networks to accelerate an inclusive and sustainable digital transformation in coffee farming managed by women.